ECONOMETRIC ANALYSIS OF MACROECONOMIC INDICATORS OF THE REPUBLIC OF KARAKALPAKSTAN - Abdullaev Ulmas Alisherovich (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
This article provides a correlation and regression analysis of the main economic indicators of the Republic of Karakalpakstan using Ridge regression, LASSO and least squares methods. The actual and theoretical values of the gross regional product of the Republic of Karakalpakstan were studied and the obtained statistical data were checked for the presence of a normal distribution law according to the Harke-Bar criterion.